An Analysis of Conditional Sentence Errors Made by Eleventh-Grade Students of the Tourism Services Department at SMKN 1 Samarinda - Yunita Sinaga (Indonesian Journal Publisher, 2026)
This study focuses on learners’ errors in using English conditional sentences. The objectives of this research were to identify the types of errors made by the eleventh-grade students of the Tourism Services Department at SMKN 1 Samarinda in using conditional sentences and to determine the most frequent type of error. This study employed a descriptive qualitative research design. The population consisted of 30 eleventh-grade students of the Tourism Services Department at SMKN 1 Samarinda in the academic year 2025/2026, and all students were taken as the sample. The instrument used was a written completion-type test on conditional sentences. The data were analyzed descriptively using illustrations, facts, statements, tables, frequencies, and percentages. The findings revealed that the students made two main types of errors: morphological and syntactical errors. These errors included mistakes in using modal auxiliaries, suffixes -s, main verb forms, and tenses. Based on error classification, the errors fell into omission, addition, and misformation, with misformation errors occurring most frequently. In terms of conditional sentence types, past unreal conditional sentences showed the highest error percentage (52.34%), followed by present unreal conditionals (40.23%) and future probable conditionals (25.69%). These findings indicate that conditional sentences, especially past unreal conditionals, remain challenging for vocational high school students.